2013
DOI: 10.1088/0004-637x/770/1/65
|View full text |Cite
|
Sign up to set email alerts
|

The Outburst Decay of the Low Magnetic Field Magnetar SGR 0418+5729

Abstract: We report on the long term X-ray monitoring of the outburst decay of the low magnetic field magnetar SGR 0418+5729 , using all the available X-ray data obtained with RXTE, Swift, Chandra, and XMM-Newton observations, from the discovery of the source in June 2009, up to August 2012. The timing analysis allowed us to obtain the first measurement of the period derivative of SGR 0418+5729: P = 4(1) × 10 −15 s s −1 , significant at ∼ 3.5σ confidence level. This leads to a surface dipolar magnetic field of B dip 6 ×… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
131
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 206 publications
13
131
1
1
Order By: Relevance
“…In the case of a white dwarf close to the critical mass, this new lower limit gives a very stringent constraint on the spindown rate of SGR 0418+5729,Ṗ = 4 × 10 −16 <Ṗ < 6 × 10 −15 , which we submit for observational verification. Indeed, after the submission of this work, Rea et al (2013) reported the confirmation of the spindown rate of SGR 0418+5729,Ṗ = 4 × 10 −15 , at 3.5 sigma confidence level. This measurement fully confirms the results of Malheiro et al (2012), see Eq.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In the case of a white dwarf close to the critical mass, this new lower limit gives a very stringent constraint on the spindown rate of SGR 0418+5729,Ṗ = 4 × 10 −16 <Ṗ < 6 × 10 −15 , which we submit for observational verification. Indeed, after the submission of this work, Rea et al (2013) reported the confirmation of the spindown rate of SGR 0418+5729,Ṗ = 4 × 10 −15 , at 3.5 sigma confidence level. This measurement fully confirms the results of Malheiro et al (2012), see Eq.…”
Section: Discussionmentioning
confidence: 74%
“…As we show below, these predictions can be improved by considering realistic white dwarf parameters instead of fiducial values. It is important to mention at this point that, after the submission of this work, Rea et al (2013) presented the X-ray timing analysis of the long-term monitoring of SGR 0418+5729 with RXTE, Swift, Chandra, and XMM-Newton, which allowed the determination of the spindown rate of SGR 0418+5729,Ṗ = 4 × 10 −15 . These results confirm both our prediction given by Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic field measured from the long-term spin down of Swift J1822.3−1606 is 1.35 × 10 13 G. This is the second lowest spin-down inferred magnetar dipolar magnetic field and is about a factor of two higher than the lowest measured value, 6.1 × 10 12 G of SGR 0418+5729 (Rea et al 2013). However, since pulsar timing is only sensitive to the surface dipolar component of the field, the true magnetic field of the magnetar could be significantly higher than the value measured from pulsar timing if the toroidal component is much higher than the poloidal component or if the poloidal field has significant multipolar contributions.…”
Section: Post-outburst Spin-down Behaviormentioning
confidence: 68%
“…∼ 6 × 10 12 G; Rea et al 2013). Simulations of magnetic field evolution in neutron stars with different initial field strength and configuration have shown that, a relatively old magnetar such as SGR 0418+5729 despite its low surface dipolar field, might still harbor a sufficiently intense internal/crustal toroidal field to give rise to outbursts and short X-ray bursts (Turolla et al 2011).…”
Section: Introductionmentioning
confidence: 99%